Interactive effective of land configuration and irrigation scheduling on yield attributes, yield, water use efficiency and economics of quinoa (Chenopodium quinoa) under Vertisols of Southern Eastern Plain Zone of Rajasthan - Monika Choudhary; J.P. Tetarwal; Anju Bijarnia; Roshan Kumawat; Bahnu Pratap Ghasil; Ashish Raja Jangid (Annals of Agricultural Research, 2022)
A study was initiated on quinoa (Chenopodium quinoa) during rabi season 2019-20 in clay loam soil at IFS Farm, Agriculture Research Station, Ummedganj, Kota (Agriculture University, Kota), including three land configuration (i.e. broad bed & furrow, ridge & furrow and flat bed techniques) and three irrigation scheduling (i.e. one irrigation at 20-25 DAS, two irrigation at 20-25 & 55-60 DAS and three irrigation at 20-25, 55- 60 & 90-95 DAS) arranged in split plot design with four replications. Results reveal that the three broad bed & furrow technique with three irrigation levels number of panicles (30.25), weight of main panicle (54.15 g), weight of primary panicle (4.13 g), grain yield (3072 kg ha-1), biological yield (3494 kg ha-1), gross return (`186901 ha-1), net returns (`147959 ha-1) and B:C ratio (3.80) significantly higher compared to rest of the treatment combinations, but water use efficiency (33.50 kg/ha-mm) and water productivity (`146.28 m-3) significantly higher with broad bed & furrow with one irrigation level.